A proposal for teaching the perfect aspect associated with the past tense to Brazilian learners of English as an additional language - Alves, Matheus Gomes; Machado, Fernanda Costa da Silva; Nespoli, Juliana Barros (The ESPecialist, 2025)
The main goal of this work is to contribute to the teaching of the perfect aspect in the context of English as an additional language to Brazilian learners. The specific goal is to propose and evaluate a set of activities designed to teach this aspect, specifically the existential perfect (EP), related to the past tense. The methodological procedures of this work consist of identifying the objectives of each of the activities presented and investigating their relevance in relation to the proposal of works in the linguistic literature that deal with the description/teaching of the perfect (Alves, Machado e Nespoli, 2020; Comrie, 1976). The results show that through categorization exercises (spatial orientation of events), pattern induction (generalization from a small corpus about the form, use and meaning of the past perfect), paraphrasing (rewriting sentences in the past perfect using other morphological forms), transliteration of spatially oriented events into linguistically ordered events and identification of the notions of anteriority and posteriority, the perfect aspect related to the past tense can be presented to Brazilian learners of English as an additional language.